Production of thermostable L2 lipase using recombinant Pichia pastoris - Shahidan, Noor Hidayah (2012)
Thermostable lipases are widely used for various industrial applications, such as in the production of detergents, oleo chemical industry, food-processing as well in dairy and milk productions. Recombinant Pichia pastoris strain GS115 harbouring L2 lipase gene under constitutive expression of glyceraldehyde-3-phosphate (GAP) was subjected to a series of batch cultivation studies at shake-flask scale (100 mL) and in 7.5 L bioreactor. Batch cultivation studies at shake-flask scale were conducted to investigate the effect of different carbon sources on the expression level of L2 lipase and growth of P. pastoris. Growth of P. pastoris at 2% (w/v) glucose concentration gave the highest lipase activity. Other carbon sources were also tested for growth; oleic acid, trehalose, glycerol, lactose, methanol and sorbitol in which it was observed that 1% (v/v) glycerol produced the highest L2 lipase activity of 34 U/mL. In addition, study on fifth grade molasses as potential carbon source revealed that the highest activity of thermostable L2 lipase of 40 U/mL occurred when the concentration of fifth grade molasses was set at 2% (w/v). Growth of the recombinant on the remnant of sugar refinery process, mud cake produced little or zero expression level of L2 lipase and poor growth of P. pastoris, showing that it was not an effective carbon source. Study conducted on different sugar components of the molasses which were sucrose, maltose, glucose, and fructose showed that the cultivation on fructose led to the highest expression of L2 lipase of 50 U/mL among growth on other carbon sources, followed by growth of P. pastoris cells on glucose. A preliminary study of batch cultivation of recombinant P. pastoris was performed using medium containing 2% (w/v) glucose as carbon source in 7.5 L bioreactor with the following parameters: controlled dissolved oxygen tension (DOT) 35%, controlled pH 6.0, 1 vvm, temperature 30°C, 30 h inoculum age, and resulted in 60 U/mL of lipase activity at 24 h of cultivation time. Batch cultivation studies were also conducted using different carbon sources namely glycerol, fifth grade molasses and mixture of glycerol and the fifth grade molasses, which produced 56, 120, and 60 U/mL of lipase activity, respectively. Further optimization studies were conducted for the selected parameters with cultivation medium containing fifth grade molasses as main carbon source:controlled pH at 6.0 and uncontrolled pH (with initial pH at 6.0), inoculum age,controlled DOT, and molasses concentration. Optimized condition with fifth grade molasses as main carbon source produced 120 U/mL when cultivation conditions were set at 35% air saturation, initial pH 6.0, 30 h of inoculum age, and 2% (w/v) of fifth grade molasses concentration. This study showed that the constitutive pGAP expression system of P. pastoris is inducible by various carbon sources; therefore, it offers flexibility for diverse expressions of heterologous proteins.